RESEARCH STATUS: THE WORKSHOPS OF THE GLOBAL WORLD, TEXTILE MAQUILA AND CALL CENTERS IN CENTRAL AMERICA - Piedra Guillén, Nancy (2022)
This article presents a critical balance of the research that has been carried out in the last three decades on the subject of work (i.e. labor); specifically those studies that analyze the transformations in the world of work, to work in the textile “maquila” sector and call centers. Our literature review focuses on these two economic sectors because it responds to a research project whose theme revolves around the working conditions and employment of people working in the textile “maquila” sector and call centers. This focus considers both as two clear examples of socioeconomic activities that respond to the process of globalization of which we are a part today and live the consequences derived from this socioeconomic model. The textile “maquila” is part of new forms ofwork which originated at the end of the 20th century, anchored in the logic of production chains, while call centers are part of the process of outsourcing production in the 21st century, based on the promotion of contracting services. Both sectors contribute to the development of the tertiarization of the economy in the Costa Rica.